Advanced spectroscopic imaging techniques for X-nuclei cardiac magnetic resonance imaging - Tyler, A (2021)
Changes to cardiac metabolism are an important component of heart failure. Understanding these metabolic changes is therefore critical to developing treatments for the failing heart, particularly pharmaceuticals, or other interventions, which aim to restore normal metabolism. A combination of hyperpolarized 13C and 31P magnetic resonance spectroscopic imaging (MRSI) enables quantification of both the substrate usage (13C) and energy output (31P) of cardiac metabolism, allowing a full picture of the metabolic state of the heart to be built up.